Harmonisasi Peraturan Perundang-Undangan dan Standar Materi Muatan: Analisis Inkonsistensi Vertikal antara Peraturan Presiden No. 74/2013 dan Peraturan Daerah Kota Sukabumi No. 13/2015 tentang Larangan Minuman Beralkohol - Intan Nailul Muna; Fahri Azhar; Jihan Rupa Puspa Ayu (PT. Hasba Edukasi Mandiri, 2025)
The regulation of alcoholic beverages in Indonesia reveals significant issues related to the harmonization of laws and regulations, particularly between the central government and local governments. Following the annulment of Presidential Decree Number 3 of 1997, the central government enacted Presidential Regulation Number 74 of 2013 on the Control and Supervision of Alcoholic Beverages, which adopts a permissive yet controlled regulatory approach. However, in practice, several local governments have enacted regulations with substantially different approaches, one of which is Sukabumi City Regional Regulation Number 13 of 2015 that imposes a total prohibition on alcoholic beverages. This divergence has resulted in vertical inconsistency, undermining the principle of the hierarchy of laws and regulations within the national legal system. This study aims to analyze the level of substantive inconsistency between Presidential Regulation Number 74 of 2013 and Sukabumi City Regional Regulation Number 13 of 2015, to examine the underlying factors contributing to the lack of vertical harmonization, and to assess the role of regional regulation evaluation mechanisms in minimizing normative conflicts. This research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the inconsistency between the two regulations is both substantive and structural, stemming from differing policy paradigms, weak implementation of the principles of good legislative drafting, and inadequate coordination between central and local governments. Therefore, optimizing both preventive and repressive evaluation mechanisms of regional regulations is essential to achieving vertical harmonization and maintaining the coherence of the national legal system.